Information System for Processing Data of Swallow's Nests at Father Jimris's Swallow House Prabumulih City - Dhea Natasya; Yuntari Purba Sari; Nurmayanti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Father jimris' swallow house is a rolling business in the dragon-pineapple industry located in the village of the prabumutown. The date-processing process in the Mr. Jimris' home is still done by hand, causing employees or old employees to do work, and this research is aimed at creating an application or a swallow's nest data processing system using PHP programming languages and mysql as databases. The development method used is rads (rapid aplication development) consisting of need planning, design and application processes. The results of this study are expected to make it easier for employees to process and access data and be able to make data processing more effective and efficient